BDNF and Schizophrenia: From Neurodevelopment to Neuronal Plasticity, Learning, and Memory - Nieto, Rodrigo; Kukuljan, Manuel; Silva, Hernan (Frontiers in Psychiatry, 2013)
Brain Derived Neurotrophic Factor (BDNF) is a neurotrophin that has been related not only to neurodevelopment and neuroprotection, but also to synapse regulation, learning and memory. Research focused on the neurobiology of schizophrenia has emphasized the relevance of neurodevelompental and neurotoxicity-related elements in the pathogenesis of this disease. Research focused on the clinical features of schizophrenia in the past decades has emphasized the relevance of cognitive deficits of this illness, considered a core manifestation and an important predictor for functional outcome. Variations in neurotrophins such as BDNF may have a role as part of the molecular mechanisms underlying these processes, from the neurodevelopmental alterations to the molecular mechanisms of cognitive dysfunction in patients with schizophrenia.